1995
DOI: 10.2214/ajr.165.1.7785572
|View full text |Cite
|
Sign up to set email alerts
|

Primary bone tumors: value of MR angiography for preoperative planning and monitoring response to chemotherapy.

Abstract: OBJECTIVE. The purposes of our study were to investigate the use of MR angiography with two-(2D) and three-dimensional (3D) displays in evaluating vascular morphohogy of musculoskeletal neoplasms for preoperative planning of limb-salvage surgery and to assess the use of MR angiography for monitoring changes in neovascularity and evaluating response to chemotherapy. SUBJECTS AND METHODS. We

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…For this purpose, conventional MR sequences are frequently entirely adequate in defining the full extent of a tumor, its relationship to the adjacent neurovascular bundle, and nearby joints (1). However, MR imaging may also be used for the roles of detection, characterization, and assessment of a tumor after treatment (both after neoadjuvant therapy before surgery for the assessment of treatment response and after surgery for assessment of postsurgical residual or recurrent disease) (2)(3)(4)(5)(6). The advent of chemical shift MR imaging (in-phase and opposed-phase imaging), diffusionweighted (DW) imaging, perfusion imaging, and MR spectroscopy has advanced the role of MR for characterizing lesions for malignancy and assessing lesions after treatment.…”
Section: Essentialsmentioning
confidence: 99%
“…For this purpose, conventional MR sequences are frequently entirely adequate in defining the full extent of a tumor, its relationship to the adjacent neurovascular bundle, and nearby joints (1). However, MR imaging may also be used for the roles of detection, characterization, and assessment of a tumor after treatment (both after neoadjuvant therapy before surgery for the assessment of treatment response and after surgery for assessment of postsurgical residual or recurrent disease) (2)(3)(4)(5)(6). The advent of chemical shift MR imaging (in-phase and opposed-phase imaging), diffusionweighted (DW) imaging, perfusion imaging, and MR spectroscopy has advanced the role of MR for characterizing lesions for malignancy and assessing lesions after treatment.…”
Section: Essentialsmentioning
confidence: 99%
“…Short tau (time) inversion recovery imaging allows more precise depiction of tumors than spinecho sequences. [25][26][27][28] Several studies comparing scintigraphy with MRI have demonstrated that MRI is more sensitive and more specific than scintigraphy, [29][30][31][32] but to date there are few reports available assessing the potential of TB-MRI. 33 Eustace et al 34 compared TB-MRI and scintigraphy in detecting skeletal metastases in 49 patients with solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In some centers, MR angiography has replaced conventional angiography in the preoperative evaluation of tumor vascularity because it is noninvasive and provides good visualization of peripheral vascular branches and tumor neovascularity in patients [17].…”
Section: Technical Considerationsmentioning
confidence: 99%